Une expérience de formation pratique des futurs-maîtres centrée sur l’auto-formation - Allard, Gaétan Y. (Canadian Journal of Education/Revue canadienne de l’éducation, 1977)
An experimental program for the practical training of future teachers has been ongoing in Sherbrooke schools for the past five years. The purpose of this study is to determine the sociological implications of the new training period based on self-instruction, its relevance, and its effectiveness. The training program is a well-structured one, but one which allows the student to progress at his own rate. Such structuring gives the student frequent feedback from the school system regarding his progress and assures him of the aid he will need in order to develop into a confident and dynamic teacher. The yearly evaluations have been compared with the results of a study of former students who have been teaching since they finished their course. The system has been very favorably received, as much for its educational relevance within the school system as for the quality of its practical training.